PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA - Muslimah Muslimah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The purpose of this study was to find out how your legal protection that is given to the child victims of domestic violence, as well as what factors led to acts of violence against children in the household. The implementation of the legal protection of children who are victims of domestic violence has been carried out in accordance with child protection legislation. The causative factors of violence against children in the household minimized as much as possible and hope to the parties involved, especially the parents in order to perform its role as a parent as well as possible, so that will not happen the things that are not desirable as violence against children.